PELATIHAN PADA KELUARGA SEBAGAI PENGAWAS MINUM OBAT UNTUK PENCEGAHAN TUBERKULOSIS RESISTEN OBAT MENSUKSESKAN SDGS KETIGA - Saraswati Laksmi Dewi (Jurnal Sutramas, 2025)
Multidrug-resistant tuberculosis (MDR-TB) remains a public health crisis and threat globally, although the incidence of TB is falling at about 2% per year. The main cause of MDR-TB is the low patient adherence to the lifelong TB regimen. High pill burden with long-course treatment simultaneously induces low adherence of the patient to continue the TB regimen. The patient should take four types of TB drugs for at least 6 months. Family support in the management of TB is absolutely needed to alleviate the incidence of TB multidrug resistance. Drug resistance emerges when anti-TB medicines are used inappropriately, through incorrect prescription by health care providers, poor quality drugs, and patients stopping treatment prematurely. The objective of this program is to educate the TB patient's family in monitoring and assisting the patient in taking the TB drug every day and reporting any side effects of the TB drug as soon as possible to prevent low adherence to the treatment. The planned methods are to train the patient's family to monitor the patient's adherence and to assist with treatment at home.